Grammatical Subjects in Method Section of Psychology and Chemistry Research Articles - Ebrahimi, Seyed Foad; Heng, Chan Swee (Widya Mandala Catholic University Surabaya, 2018)
This study intends to investigate the realizations and functions of grammatical subject in the method section of research articles across disciplines from hard and soft sciences. To this end, 20 method sections of research articles from two disciplines, namely Psychology and Chemistry, were selected and analyzed. The data were selected from high impact journals indexed in Thompson and Reuters and published by Elsevier. The data were analyzed based on Ebrahimi’s recent analytical framework for the analysis of grammatical subject. The results highlighted noticeable disciplinary differences concerning realizations of the research-related and self-mention grammatical subjects. The results of this study could act as a guide to aid novice writers, especially non-native novice writers from these two disciplines with regard to the use of grammatical subject which serves as an important point in the navigation of subsequent ideas in a message. The findings also stressed that writers need to consider the writing style of their disciplines in realizing linguistic features, such as grammatical subject functionally.